2017
DOI: 10.1371/journal.pone.0171484
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cyclist crashes in Italy using latent class analysis and association rule mining

Abstract: The factors associated with severity of the bicycle crashes may differ across different bicycle crash patterns. Therefore, it is important to identify distinct bicycle crash patterns with homogeneous attributes. The current study aimed at identifying subgroups of bicycle crashes in Italy and analyzing separately the different bicycle crash types. The present study focused on bicycle crashes that occurred in Italy during the period between 2011 and 2013. We analyzed categorical indicators corresponding to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 85 publications
3
15
0
Order By: Relevance
“…Al-Balbissi, 2003;de Winter & Dodou, 2010;Nallet et al, 2010;€ Ozkan & Lajunen, 2006;Prati, 2018;Rhodes & Pivik, 2011;Tom & Granie, 2011). Concerning mobility patterns, we found that men cyclists are more likely to be involved in crashes in rural areas (Hypothesis 2) and previous research documented that, in Italy, the risk of fatal injury is higher in rural areas than in urban areas (Prati, De Angelis, Mar ın Puchades, Fraboni, & Pietrantoni, 2017;. In the present study, we also found some evidence of systematic differences across gender in risky behaviours and violations (Hypothesis 6).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Al-Balbissi, 2003;de Winter & Dodou, 2010;Nallet et al, 2010;€ Ozkan & Lajunen, 2006;Prati, 2018;Rhodes & Pivik, 2011;Tom & Granie, 2011). Concerning mobility patterns, we found that men cyclists are more likely to be involved in crashes in rural areas (Hypothesis 2) and previous research documented that, in Italy, the risk of fatal injury is higher in rural areas than in urban areas (Prati, De Angelis, Mar ın Puchades, Fraboni, & Pietrantoni, 2017;. In the present study, we also found some evidence of systematic differences across gender in risky behaviours and violations (Hypothesis 6).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, our results reveal a higher occurrence of crashes among men cyclists on weekends and during the summer period. Severity of bicycle crashes results higher on rural roads than on urban roads, which may also be an explanation for a higher occurrence of fatal crashes among men (Boufous, de Rome, Senserrick, & Ivers, 2012;Moore, Schneider, Savolainen, & Farzaneh, 2011;Prati, De Angelis, et al, 2017;. Ideals of hegemonic masculinity shape the patriarchal character of sport in Western countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Transportation Research Board Access Management Manual [40], traffic conflict points occur where vehicle paths cross, merge or weave, and the drivers take evasive actions to avoid collision. In this research, all possible conflict points between the motorized vehicles and bicycles, have been considered-bicycle-to-bicycle conflicts were not considered because their frequency is low in Italy [41]. In Figure 4, the detected conflict points at a four-lane four-arm intersection are red-there were 56.…”
Section: Summary Approachmentioning
confidence: 99%
“…On European roads 31% of the cyclists' fatalities happen at junctions [16]. Several studies point to heightened risk of bicycle crashes at intersections relative to other road sections [17][18][19][20][21]. Yet, few inquiries are conducted in real environments to understand the relationships between conditions in intersections that trigger this heightened risk and physiological dimensions.…”
Section: Introductionmentioning
confidence: 99%